A Study of Purchase Intention on Apple Products - Wafa’a Bajunid Binti Sheikh Abdullah; Wang Jingbin; Wang Junhan; Wang Jingsong; Teoh Kok Ban; Jimoh Adams Lukman (Global Academia Publisher, 2022)
Apple Inc. is one of the leading brands in the enormous technology device market. The company experienced a decline in sales during the pandemic and still survived to rose again as pandemic restrictions eased. This paper examines how five key factors, namely perceived product quality, perceived price affordability, perceived ease of access, brand awareness and brand loyalty, lead to Apple’s customer purchase intention. The study employed an exploratory research design that helped us connect ideas to understand the groundwork of our analysis. The methods of data collection in this study are internet sources and structured questionnaires. There are 150 respondents who participated in this survey. The data were analyzed with descriptive statistics and inferential statistics. The findings of the study will provide new insights and contribute to customer behaviour that correlates with purchase intention. Besides that, some recommendations for Apple's improvement can be obtained through the findings of this study as well.